مستوى استخدام معلمي التلاميذ ذوي الإعاقة الفكرية للتطبيقات التعليمية في دعم تحصيلهم الدراسي - الأحمري، عبدالعزيز مساعد; القريني، تركي عبدالله سليمان (المركز القومي للبحوث غزة, 2023)
هدفت الدراسة الحالية للتعرف على مستوى استخدام معلمي التلاميذ ذوي الإعاقة الفكرية للتطبيقات التعليمية في دعم تحصيلهم الدراسي، والتعرف على مدى الاختلافات بين استجابات العينة وفقا للمتغيرات الآتية: (الجنس، المؤهل التعليمي، سنوات الخبرة). ولتحقيق أهداف الدراسة تم اتباع المنهج الوصفي. واستخدام الاستبانة أداة لجمع البيانات. وتم تطبيقها على عينة اختيرت بالطريقة العشوائية من مجتمع الدراسة المتمثل في معلمي ومعلمات التلاميذ ذوي الإعاقة الفكرية العاملين في معاهد وبرامج التربية الفكرية التابعة لوزارة التعليم في مدينة الرياض، والبالغ عددها (669). وخلصت النتائج إلى أن معلمي التلاميذ ذوي الإعاقة الفكرية "أحيانا" يستخدمون التطبيقات التعليمية. كما أسفرت عن وجود فروق ذات دلالة إحصائية في مستوى استخدام معلمي التلاميذ ذوي الإعاقة الفكرية للتطبيقات التعليمية لدعم التحصيل الدراسي للتلاميذ في تلك المجالات، تعود لاختلاف نوع العينة، وكانت تلك الفروق لصالح عينة المعلمين. كما أشارت إلى وجود فروق ذات دلالة إحصائية في مستوى استخدام معلمي التلاميذ ذوي الإعاقة الفكرية للتطبيقات التعليمية لدعم التحصيل الدراسي للتلاميذ في تلك المجالات، تعود لاختلاف المؤهل التعليمي، لصالح الحاصلين على (مؤهلات علمية أخرى). وجود فروق ذات دلالة إحصائية في مستوى استخدام معلمي التلاميذ ذوي الإعاقة الفكرية للتطبيقات التعليمية لدعم التحصيل الدراسي للتلاميذ في تلك المجالات، تعود لاختلاف عدد سنوات الخبرة، لصالح ذوي الخبرة (من 16 سنة فأكثر). ومن أبرز التوصيات: العمل على تأهيل المتخصصين في مجال تعليم ذوي الإعاقة الفكرية في الجامعات والكليات بكيفية توظيف التطبيقات التعليمية في العملية التعليمية، وعقد البرامج التدريبية وبرامج التطوير المهني للمعلمين والمعلمات العاملين في برامج ومعاهد التربية الفكرية. This study aimed to identify the level of use of educational applications by teachers of students with intellectual disabilities to support their academic achievement, and the extent of differences between the sample responses according to the variables: (gender, educational qualification, years of experience). The study followed the descriptive approach, and used a questionnaire. It was applied to a random sample (669) of teachers of students with intellectual disabilities In institutes affiliated to the Ministry of Education in Riyadh. The most important results: Teachers "sometimes" use educational applications. There are differences in the level of using educational applications to support students' academic achievement due to the difference in the sample type (in favor of teachers), due to the difference in educational qualifications in favor of those with (other educational qualifications), And due to the difference in the number of years of experience in favor of a sample of experienced (16 years and over). The most important recommendations are: Working to qualify specialists in the field of education for people with intellectual disabilities in universities and colleges on how to employ educational applications in the educational process, which contributes to its practice in the future in reality. Holding training programs and professional development programs for male and female teachers who are working in intellectual education programs and institutes, through which educational applications are introduced and how to benefit from them; to support their students' skills and achieve their goals. Providing tools and equipment related to running and displaying educational applications.
Keywords: التربية الخاصة -- التطبيقات التعليمية -- التربية الفكرية -- التحصيل الدراسي -- السعودية